STUDI KOMPARASI METODE WEIGHT PRODUCT DAN SIMPLE ADDITIVE WEIGHTING DALAM SISTEM PEMILIHAN ALAT KONTRASEPSI BERBASIS WEB - Pangara, Takdir S; Anshori, Yusuf; Amriana, Amriana (Fakultas Teknik, Universitas Tadulako, 2021)
Controlling birth is closely related to the use of contraceptives for their partners. However, the problem they often face is that they struggle to choose an effective contraceptive that suits their body condition. This is not only caused by the limited methods available but also because they do not know the requirements and safety of these contraceptive methods. This study aims to implement and analyze the comparison of the Weight Product (WP) method and the Simple Additive Weighting (SAW) method in a web-based contraceptive selection decision-making system. This system can work well in determining the right contraception for a married couple. In the time testing process, the implementation of the SAW method has an average execution time of 1.8784 s while the WP method has an average execution time of 0.3340 s. Based on the research results, the WP method is slightly faster than the SAW method in carrying out the calculation process in the decision support system for the selection of contraceptives.Â